Whole-genome sequencing, phenotypic characterization, and antifungal susceptibility profiles of three Aspergillus hortae clinical isolates from Colombia - Santiago Marin-Carvajal; Mariana Quiceno Torres; Maria Camila Zuleta; Susana Torres; Álvaro Rúa-Giraldo; Ana Maria García; Clayton L. Borges; Angela Maria López; Juan G. McEwen; Orville Hernández; Oscar Mauricio Gómez (PLoS ONE, 2026)
The Aspergillus genus comprises fungi that are widely distributed in nature. Several Aspergillus sections are important for recycling organic matter; while the Fumigati section is classically associated with compost, the Terrei section also plays a relevant role in this process. Aspergillus hortae is a species from this section that has been isolated from clinical samples, but its role as a pathogenic agent is unclear. In this study, we analysed three clinical isolates of A. hortae from Colombia, initially misidentified as A. terreus . Morphological characterization at 26 °C and 37 °C confirmed its thermotolerant nature. Whole-genome sequencing enabled accurate species identification and revealed phylogenetic divergence from the reference genome. Antifungal susceptibility testing (EUCAST broth microdilution) showed intrinsic resistance to amphotericin B (MIC 2–4 mg/L) and susceptibility to azoles (MIC 0.25–1 mg/L). A mutation (M769K) in the MelA ortholog of a hypopigmented isolate, which had the lowest MIC value for AmB (2 mg/L), was identified. This study presents the morphological characterization, molecular typing through whole-genome analysis and identification of susceptibility profiles to azoles and amphotericin B of three clinical isolates of A. hortae from Colombia.